TI_GERICHTE 52.2016.399 vom 27. März 2017 , Commesse pubbliche. Criteri d'idoneità dell'offerente ex art. 34 RLCPubb/CIAP - TI Tribunale d'appello (2017)
Commesse pubbliche. Criteri d'idoneità dell'offerente ex art. 34 RLCPubb/CIAP